PERUBAHAN STATUS GIZI BALITA PADA PROGRAM EDUKASI DAN REHABILITASI GIZI - Ariska, Yusi; Kustiyah, Lilik; Widodo, Yekti (Jurnal Gizi dan Pangan, 2015)
ABSTRACTThis study was aimed to analyze factors that influence the change in nutritional status of children under-five years who participated in Nutrition Education and Rehabilitation Program. This research used secondary data with a pre-post intervention study (one group before and after intervention design) of 141 subjects. Six months intervention program which applied to the children consisted of provision of complementary feeding and supplement of zinc along with nutrition and health education for the mothers. This research conducted at District of East Kutai, Province of East Kalimantan. The average WAZ score of subjects after participating had increased significantly (-1.9±0.6) compared before participating in this program (-2.3±0.5) (p<0.05). Subjects with a good appetite tended to increase WAZ score four times than the worse one, while diarrhea subjects tended to have 0.3 times smaller WAZ score increase than non-diarrhea subjects.Keywords: children under-five years, diarrhea, nutrition education, rehabilitationABSTRAKPenelitian ini bertujuan untuk menganalisis faktor-faktor yang berpengaruh terhadap perubahan status gizi balita pada Program Edukasi dan Rehabilitasi Gizi. Penelitian ini menggunakan data sekunder. Desain yang digunakan adalah pre-post intervention study dengan jumlah subjek sebanyak 141 balita. Intervensi yang diberikan pada balita berupa pemberian makanan tambahan bersama, suplemen zink, dan penyuluhan gizi dan kesehatan bagi ibu balita. Intervensi tersebut diberikan selama 6 bulan dan dilaksanakan di Kabupaten Kutai Timur, Provinsi Kalimantan Timur. Rata-rata z-score BB/U balita setelah mengikuti Program Edukasi dan Rehabilitasi Gizi adalah nyata lebih tinggi (-1,9±0,6) dibandingkan sebelum mengikuti program tersebut (-2,3±0,5) (p<0,05). Anak balita yang memiliki nafsu makan yang baik cenderung mengalami kenaikan status gizi (BB/U) empat kali lebih besar daripada balita yang nafsu makannya kurang baik. Balita yang mengalami diare memiliki kecenderungan 0,3 kali lebih kecil mengalami kenaikan status gizi (BB/U) dibandingkan yang tidak mengalami diare.Kata kunci: balita, diare, edukasi gizi, rehabilitasi